Nanomaterials Manipulate Macrophages for Rheumatoid Arthritis Treatment - Li, Shuang; Su, Jin; Cai, Wei; Liu, Jian-xin (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is a chronic, progressive, systemic inflammatory autoimmune diseases, characterized by synovial inflammation, synovial lining hyperplasia and inflammatory cell infiltration, autoantibody production, and cartilage and bone destruction. Macrophages are crucial effector cells in pathological process of RA, which can interact with T cell and B cell and fibroblast-like synovial cell (FLS) to produce large amounts of cytokines, chemokines, digestive enzymes, prostaglandins, and reactive oxygen species to accelerate bone destruction. Therefore, the way that the application of nanomaterials to target RA joint macrophages has far-reaching therapeutic implications for RA. A number of shortcomings are existed in the current clinical therapy for RA patients including severe negative side effects, poor selectivity, frequent and high-dose of medication, which have dramatically encourage the development and application of targeting drug delivery system in the treatment of RA. Recently, the obvious therapeutic effects on RA were obtained by the use of various kinds of nanomaterials to manipulate the macrophages based on intravenous injection (active or passive targeting), oral administration, percutaneous absorption, intraperitoneal, and intra-articular injection, which possesses several advantages such as high-precision targeting on macrophages and synovial tissue of joint. In this review, the manipulate mechanisms of nanomaterials on macrophages are analyzed, and the prospect of clinical application is also discussed, which paves a reference for the research on the therapy of RA based on targeting of macrophages.